2022
DOI: 10.1007/s00426-022-01659-x
|View full text |Cite
|
Sign up to set email alerts
|

Explicit vs. implicit spatial processing in arrow vs. eye-gaze spatial congruency effects

Abstract: Arrows and gaze stimuli lead to opposite spatial congruency effects. While standard congruency effects are observed for arrows (faster responses for congruent conditions), responses are faster when eye-gaze stimuli are presented on the opposite side of the gazed-at location (incongruent trials), leading to a reversed congruency effect (RCE). Here, we explored the effects of implicit vs. explicit processing of arrows and eye-gaze direction. Participants were required to identify the direction (explicit task) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 76 publications
1
9
1
Order By: Relevance
“…For example, the original explanation for the effect (Cañadas & Lupiáñez, 2012; Marotta et al, 2018) proposed that participants interpret gaze-oriented inward (i.e., on incongruent trials) as a face potentially making eye contact with them. Nevertheless, no reversed congruency effect was observed with gaze in a series of experiments in which participants had to discriminate the color of the eyes (rather than gaze direction; Narganes-Pineda et al, 2021), the results in this implicit task being inconsistent with the eye-contact hypothesis, and suggesting that the automatic processing of the eye-gaze direction (Driver et al, 1999) does not affect the behavioral outcomes of our paradigm. Alternatively, and without evoking any “looking at me” attribution, Edwards et al (2020) proposed that gaze-oriented inward might generate an episode of joint attention where both the participant and the gaze cue look at fixation, facilitating participants’ performance on incongruent trials.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…For example, the original explanation for the effect (Cañadas & Lupiáñez, 2012; Marotta et al, 2018) proposed that participants interpret gaze-oriented inward (i.e., on incongruent trials) as a face potentially making eye contact with them. Nevertheless, no reversed congruency effect was observed with gaze in a series of experiments in which participants had to discriminate the color of the eyes (rather than gaze direction; Narganes-Pineda et al, 2021), the results in this implicit task being inconsistent with the eye-contact hypothesis, and suggesting that the automatic processing of the eye-gaze direction (Driver et al, 1999) does not affect the behavioral outcomes of our paradigm. Alternatively, and without evoking any “looking at me” attribution, Edwards et al (2020) proposed that gaze-oriented inward might generate an episode of joint attention where both the participant and the gaze cue look at fixation, facilitating participants’ performance on incongruent trials.…”
contrasting
confidence: 54%
“…However, recent evidence with the paradigm has made important advances. The effect occurs later in processing (Marotta et al, 2019) and later in the development (Aranda-Martín et al, 2021), and seems more related to the capacity of gaze to attract attention out of the task in congruent trials (Hemmerich et al, 2021), instead of resulting from an eye-contact attribution (Narganes-Pineda et al, 2021) or a joint attention episode (Aranda-Martín et al, 2021). In addition, the present study supports that this social-specific effect coexists with a domain-general spatial orienting mechanism commonly evoked by eye gaze and nonsocial stimuli like arrows.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, surprisingly, with social stimuli (full faces and cropped eyes), slower RTs and more errors were observed for congruent versus incongruent trials. This effect observed on social stimuli, referred to by the authors as reversed congruency effect (Cañadas & Lupiáñez, 2012), has been repeatedly replicated since then (Aranda-Martín et al, 2022; Edwards et al, 2020; Ishikawa et al, 2021; Jones, 2015; Marotta et al, 2018, 2019; Narganes-Pineda et al, 2022; Román-Caballero et al, 2021a, 2021b; Torres-Marín et al, 2017). Recently, the same pattern of standard and reversed congruency effects, for arrows and gaze, respectively, has been replicated through a within-participant counterbalanced blocked design (Marotta et al, 2018).…”
mentioning
confidence: 72%
“…the right-gazing target at the right), they suggested that the target led observers' attention away from the stimulus display area, slowing down the responses in congruent trials. Although it is still debated which explanation is more plausible (Aranda-Martín et al, 2022;Narganes-Pineda et al, 2022;Tanaka et al, 2022), most importantly, these accounts emphasise the unique status of eye gaze in social communication.…”
Section: Eye Gaze Is Not Specialmentioning
confidence: 99%